A Futher Note on the Theory of Inflation - Okun, Arthur M. (Review of Economic Studies, 1953)
Journal Article A Further Note on the Theory of Inflation Get access Arthur M. Okun Arthur M. Okun New Haven, Conn. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Pages 244–245, https://doi.org/10.2307/2295781 Published: 01 January 1953